A Generic Data Generation Framework for Short Circuit Detection Training of Neural Networks - Wang, Minxiao; Kordowich, Georg; Jäger, Johann (Conference Proceedings, 2 – 4 November 2022 in Kassel, Germany, 2022)
Artificial Neural Networks excel in pattern recognition tasks and can therefore be used to identify short circuits in power systems. As short circuits do not frequently occur in real world grids, simulation data must be used to train neural networks. This paper describes a framework that can be used to automatically create large datasets for the training process of Neural Networks. Tests show that the framework is fast, adaptable, and works out of the box for most grid models. Additionally, a short circuit detection training is presented, that proves the applicability for Neural Network training purpose

A hybrid Protection Scheme based on Deep Reinforcement Learning - Kordowich, Georg; Jaworski, Michael; Lorz, Tobias; Scheibe, Christian; Jäger, Johann (2022 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe), 2022)
The growth of distributed renewable energy re-sources pushes classic protection schemes to their limits. An automated workflow is necessary to handle the volatility of future power systems characterized by constantly changing network states. Therefore a hybrid, deep reinforcement learning based protection scheme is proposed in this paper, which combines a single agent training for central protection with a multi agent training for a decentralized fallback.For this purpose, a training framework using a combination of PowerFactory and Python-Scripts connected via a Shared Memory is developed. The framework is used to train agents using Deep Recurrent Q-Learning. First a central protection is trained, which can then be imitated by decentral agents using only local measurements. Tests of the setup show a fast and selective response, which proves that deep reinforcement learning can indeed automatically generate a protection scheme fulfilling high requirements of dependability and security.<br

An Accessible PyTorch Implementation of Automatic Differentiation for Power System Model Parameter Identification and Optimization - Kordowich, Georg; Jäger, Johann (NEIS 2024, 2025)

An Impedance Estimation Method for High Ohmic Ground Faults in Compensated Distribution Grids - Hillen, Yannick; Kordowich, Georg; Jäger, Johann (PESS 2023; Power and Energy Student Summit, 2024)
This paper proposes a new method to determine the impedance of single phase high impedance ground faults in compensated power grids. The estimation of the ground fault impedance is achieved by switching a reactance parallel to the Petersen coil and analyzing the resulting damping of the system. The value of the damping rate, can be used to determined whether a ground fault is active and how high the impedance of that ground fault is.
Keywords: high impedance ground faults; compensated power grid; fault determination

A Systematic Evaluation of Machine Learning Methods for Fault Detection and Line Identification in Electrical Power Grids - Oelhaf, Julian; Kordowich, Georg; Perez Toro, Paula Andrea; Arias Vergara, Tomás; Maier, Andreas; Jäger, Johann; Bayer, Siming (ICASSP 2025 - 2025 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2025)
The integration of renewable energy sources into the electrical grid introduces complex challenges in fault detection and coordination of grid recovery mechanisms. Traditional relay protection systems, which operate based on static rules and predefined thresholds, are inadequate for addressing these challenges, particularly in detecting and isolating faults such as short circuits. Consequently, the conventional methodologies applied to electrical network protection frequently fail to achieve optimal performance in fault detection, especially in terms of adherence to safety standards and the selective limitation of damage. Recent research indicates that machine learning (ML)-based approaches can effectively tackle these issues; however, variations in grid configurations and analysis windows have impeded consistent comparative assessments. In this study, we assess the efficacy of various ML models in detecting electrical faults and pinpointing defective transmission lines within a 10 ms measurement interval—a critical time-frame for real-time operational viability, for the first time. The most effective model attained an F1 score of 0.991±0.018 and demonstrated a processing time of 0.342ms±0.509m
Keywords: Electrical Grid; Fault detection; Fault Line Identification; Machine Learning; Time Series

Automatisierte synthetische Störschrieberstellung in PowerFactory® für das Training eines Künstlichen Neuronalen Netzes zur Erdschlusserkennung - Conrad, Timon; Kordowich, Georg; Gaube, Sven; Kereit, Matthias; Böhme, Klaus; Jäger, Johann (VDE ETG/FNN-Tutorial 2024. Schutz- und Leittechnik, 2024)
Erdschlüsse zählen zu den verbreitetsten Fehlerarten in Mittelspannungsnetzen. Ihre Detektion stellt eine der schwierigsten Aufgabe in der Schutztechnik dar, insbesondere bei hochohmigen Erdschlüssen. Die Zuverlässigkeit konventioneller Erkennungsmethoden wird durch eine Vielzahl von Faktoren beeinflusst, darunter die Art des Fehlers, die Bodenbeschaffenheit und die Wetterbedingungen. Im Rahmen eines Projekts wird die Verwendung künstlicher neuronaler Netze für diese Aufgabe untersucht. Das Training der neuronalen Netze benötigt eine große Anzahl von Störschrieben, mit deren Hilfe es die komplexen Muster von Erdschlüssen erlernen kann. Erdschlüsse müssen aber auch von Schaltvorgängen oder anderen Fehlern unterschieden werden. Die dafür benötigte große Anzahl von Störschrieben kann mit realen Störschrieben im normalen Netzbetrieb nur in seltenen Fällen erreicht werden. Aus diesem Grund wird in diesem Poster die automatisierte Erstellung von synthetisch generierten Störschrieben durch Simulation in PowerFactory® vorgestellt. Für die Erstellung eines möglichst diversifizierten Datensatzes für ein robustes Training werden die Fehlerorte und -zeitpunkte mit verschiedenen weiteren Parametern variiert. Das verwendete Netzmodell zur Simulation basiert auf einem realen Stromnetz, für das ein Monitoring durchgeführt wird, wodurch reale Störschriebe zur Verfügung stehen. Im Verlauf des Projektes wurde das Netzmodell des realen Stromnetzes auf ein einfacheres Netzmodell reduziert, welches alle Fehlercharakteristiken des detaillierten Stromnetzes durch Parametervariationen abbilden kann. Zur Überprüfung dieses Ansatzes werden Störschriebe des realen Stromnetzes mit den Störschrieben der Simulation mit der Parametervariation verglichen, das eine stetige Verbesserung des reduzierten Netzmodells erlaubt. Von diesem reduzierten Netzmodell wird erwartet, dass es eine bessere Generalisierbarkeit des neuronalen Netzes auch auf weitere Stromnetze ermöglicht.<br
Keywords: KI; Simulation

Concept and Operation of a distributed multi-domain Power System Laboratory with HiL-capabilities - Mehlmann, Gert; Scheibe, Christian; Resch, Simon; Kordowich, Georg; Richter, Julian; Wagner, Timo; Kuri, Ananya; Richter, Michael; Jäger, Johann; Luther, Matthias (ETG-Fachbericht 170: ETG Kongress 2023, 2023)

Digitales CHiL Schutz-Testframework in Echtzeitumgebung - Löbel, Jonathan; Kordowich, Georg; Wagner, Timo; Jäger, Johann (VDE ETG-/FNN-Tutorial Schutz- und Leittechnik, 2024)
Die steigende Anzahl an Stromrichtern im elektrischen Netz führt zu wachsenden Herausforderungen für die Schutztechnik. Ihr Verhalten im Fehlerfall kann deutlich von klassischen Synchronmaschinen abweichen. Bestimmend sind dabei die Strom- und Spannungsbegrenzung, sowie die Regelung der Anlagen. Um diese Herausforderung zu erforschen, ist ein zuverlässiges, sicheres und schnelles Testsetup erforderlich, welches sich in eine digitale Substation integrieren lässt. Das Echtzeitlabor des Lehrstuhls für Elektrische Energiesysteme der FAU ermöglicht die Entwicklung eines solchen Testsetups, ohne die Integrität des Stromnetzes zu gefährden. Dabei besteht eine Kopplung von Echtzeitsimulatoren mit realen Schutzgeräten. Diese wurde über die IEC 61850-9-2 realisiert. Das Protokoll normt die digitale Kommunikation in Umspannwerken. Im Abschnitt 9-2 wird digitale Kommunikation über Samples Values (SV) reguliert. Via SV werden dabei abgetastete Messwerte von einer Merging Unit über Ethernet-Multicast veröffentlicht. Andere Geräte können diese Werte empfangen und verwerten. Die Messwerte entsprechen den Strom- und Spannungswerten der drei Phasen, sowie des Neutralleiters. Diese Methode bietet für Labore eine einfache und sichere Kommunikation zwischen mehreren Teilnehmern. Es stehen vier Universalschutzgeräte 7SX85 von Siemens zu Verfügung. Über das Simulationsprogramm RSCAD®Fx können auf dem RTDS®NovaCor Echtzeitsimulator komplexe Netze in Echtzeit simuliert werden. Zudem besteht die Möglichkeit für Schutzgeräte übliche COMTRADE Files in Echtzeit abzuspielen und so auf das Schutzverhalten zu testen. Vorhandene Regelungen und Simulationen von Stromrichtern in MATLAB/Simulink können über RT-Lab, die Benutzeroberfläche des OPAL-RT Echtzeitsimulators, in eine Echtzeitumgebung eingebettet werden. Somit kann das Verhalten der Regelung auf den Schutz getestet werden. Zudem können die SV-Streams der Echtzeitsimulatoren mit einem PC abgegriffen werden. Dies bietet die Möglichkeit neue Schutzalgorithmen zu schreiben und zu testen, ohne auf existierende Hersteller Hardware zur¨uckgreifen zu müssen.<br

Erdschlusserkennung basierend auf Künstlichen Neuronalen Netzen - Kordowich, Georg; Lorz, Tobias; Jaworski, Michael; Klumpp, Philipp; Perez Toro, Paula Andrea; Gaube, Sven; Kereit, Matthias; Böhme, Klaus; Nöth, Elmar; Jäger, Johann (12. VDE ETG-/FNN-Tutorial Schutz- und Leittechnik, 2022)
Erdschlüsse gehören zu den häufigsten Fehlern im Mittelspannungsnetz. Gleichzeitig ist insbesondere die Erkennung von hochohmigen Erdschlüssen eine der schwierigsten Aufgaben der Schutztechnik. Durch die zahlreichen Einflussparameter wie beispielsweise Fehlerursache, Bodenbeschaffenheit und Witterung auf Fehler- und Erdimpedanz können konventionelle Verfahren Erdschlüsse nicht in jedem Fall zuverlässig erkennen. In diesem Poster soll deshalb ein Konzept vorgestellt werden, das durch Verwendung von Künstlichen Neuronalen Netzen eine Ergänzung zu den etablierten Verfahren bilden soll. Durch ein Training sollen die Neuronalen Netze erlernen die komplexen Muster der Erdschlüsse zu erkennen und von anderen Schalthandlungen oder Fehlern abgrenzen können. Im Gegensatz zu konventionellen Schutzkonzepten, deren Erkennung meist von den Werten einzelner Parametern abhängt, sollen die Neuronalen Netze ein generisches Verständnis für die Muster entwickeln und so robuster und vielseitiger einsetzbar sein. Für die Generierung der Trainingsdaten ist ein möglichst akkurates Modell des entsprechenden Einsatzgebietes nötig. Mit diesem können automatisiert Simulationen durchgeführt, und Messdaten exportiert werden. Dabei werden verschiedene Fehlerorte und -zeitpunkte mit verschiedenen Parametern simuliert, um einen möglichst diversen Datensatz für ein robustes Training zu generieren. Die Messdaten aus den Simulationen werden anschließend für das Training der Neuronalen Netze verwendet. Um die Fehlererkennungsfähigkeit der Netze zu verifizieren, können diese anschließend mit Messdaten aus realen elektrischen Netzen validiert werde

Erfahrungen beim Einsatz von Neuronalen Netzen für die Erkennung von Erdfehlern im Netzbetrieb - Kordowich, Georg; Conrad, Timon; Gaube, Sven; Kereit, Matthias; Böhme, Klaus; Jäger, Johann (VDE ETG-/FNN-Tutorial Schutz- und Leittechnik, 2024)
Erdschlüsse gehören zu den häufigsten Fehlern im Mittelspannungsnetz. Gleichzeitig ist die Erkennung von hochohmigen Erdschlüssen eine der schwierigsten Aufgaben der Schutztechnik. Zahlreiche Einflussparameter wie beispielsweise Fehlerursache, Bodenbeschaffenheit und Witterung beeinflussen die Strom- und Spannungsverläufe im Erdschlussfall. Konventionelle Verfahren können Erdschlüsse nicht in jedem Fall zuverlässig erkennen. Im Rahmen eines Projektes wurden aus diesem Grund neuronale Netze mit simulierten Daten aus einem Netzmodell trainiert und anschließend in einem realen Netz eingesetzt. Das Poster präsentiert eine Analyse der Performance jener neuronalen Netze während ihrer Anwendung im realen Netzbetrieb. Die Analyse beurteilt die Leistungsfähigkeit anhand von zwei real gemessenen Datensätzen. Über mehrere Tage hinweg wurden künstlich im Netz erzeugte Erdschlüsse aufgezeichnet und die Detektionsrate der Neuronalen Netze überprüft. Des weiteren wurden über mehrere Monate hinweg Daten aus dem Netzbetrieb aufgezeichnet und Ausschnitte manuell gelabelt. Mit Hilfe realer Erdschlüsse in diesem Datensatz können Aussagen über die Performance der neuronalen Netze im realen Betrieb getroffen werden. Um diese Aussagen validieren zu können wird ein Vergleich zu einem klassischen Verfahren zur Erdschlussdetektion gezogen, um den Mehrwert eines KI-basierten Schutzsystems für Netzbetreiber durch statistische Auswertungen zu demonstrieren. Besondere Aufmerksamkeit gilt dabei auch Einschränkungen sowie spezifischen Ereignissen im Netz, die für neuronale Netzwerke eine Herausforderung darstellen.<br

Impact of Data Sparsity on Machine Learning for Fault Detection in Power System Protection - Oelhaf, Julian; Kordowich, Georg; Kim, Changhun; Perez Toro, Paula Andrea; Maier, Andreas; Jäger, Johann; Bayer, Siming (33rd European Signal Processing Conference (EUSIPCO 2025), 2025)
Germany's transition to a renewable energy-based power system is reshaping grid operations, requiring advanced monitoring and control to manage decentralized generation. Machine learning (ML) has emerged as a powerful tool for power system protection, particularly for fault detection (FD) and fault line identification (FLI) in transmission grids. However, ML model reliability depends on data quality and availability. Data sparsity resulting from sensor failures, communication disruptions, or reduced sampling rates poses a challenge to ML-based FD and FLI. Yet, its impact has not been systematically validated prior to this work. In response, we propose a framework to assess the impact of data sparsity on ML-based FD and FLI performance. We simulate realistic data sparsity scenarios, evaluate their impact, derive quantitative insights, and demonstrate the effectiveness of this evaluation strategy by applying it to an existing ML-based framework. Results show the ML model remains robust for FD, maintaining an F1-score of 0.999±0.000 even after a 50x data reduction. In contrast, FLI is more sensitive, with performance decreasing by 55.61% for missing voltage measurements and 9.73% due to communication failures at critical network points. These findings offer actionable insights for optimizing ML models for real-world grid protection. This enables more efficient FD and supports targeted improvements in FL
https://cris.fau.de/converis/publicweb/Publication/344222192
Keywords: data sparsity; fault detection; machine learning; power grid; sensor reliability

Model-based power system protection – benefits and drawbacks - Becker, Gregor; Kordowich, Georg; Jäger, Johann (IET Conference Proceedings, 2025)

Verification of neural network based power system protection schemes - Mederer, Christoph; Kordowich, Georg; Oelhaf, Julian; Maier, Andreas; Bayer, Siming; Jäger, Johann (19th IET Conference on Developments in Power System Protection (DPSP Europe 2025), 2025)
Recent studies have highlighted the potential of neural networks (NNs) to address emerging challenges in power system protection posed by the integration of distributed energy resources. While NNs have demonstrated effectiveness in fault detection, localisation, and protection coordination, their practical adoption in real-world grid environments remains limited. This limitation is primarily attributed to their "black box" nature and vulnerability to adversarial inputs. This paper presents a methodology for validating and visualising NN decisions specifically designed for power system protection tasks. The verification process employs a Mixed-Integer Linear Programming (MILP) approach, ensuring reliable NN decisions across defined input regions rather than isolated points. The decision boundaries and regions of trust are visualised through R-X diagrams, a well-established tool among protection engineers. These visualisations enhance the transparency and interpretability of NN decision-making, paving the way for secure and dependable NN-based solutions in power system protectio